Assessment Practices in Higher Education: Myths and Realities - Areekkuzhiyil, Santhosh (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Assessment is an integral part of any teaching learning process. Assessment practices have a large number of functions to perform in the context of teaching learning process. Do the contemporary assessment practices perform these functions is a critical question to be analyzed. In this paper an attempt has been made to analyze the myths and realities of the assessment practice at the higher education sector.